Telocytes Enhances M1 Differentiation and Phagocytosis While Inhibits Mitochondria-Mediated Apoptosis Via Activation of NF-κB in Macrophages - Huang, Yue-Lin; Zhang, Fei-Lei; Tang, Xue-Ling; Yang, Xiao-Jun (Cell transplantation, 2021)
Telocytes (TCs), which are a recently discovered interstitial cell type present in various organs and tissues, perform multiple biological functions and participate in extensive crosstalk with neighboring cells. Endometriosis (EMs) is a gynecological disease characterized by the presence of viable endometrial debris and impaired macrophage phagocytosis in the peritoneal environment. Here, CD34/vimentin-positive TCs were co-cultured with RAW264.7 cells in vitro. M1/M2 differentiation-related markers were detected; phagocytosis, energy metabolism, proliferation, apoptosis, and pathway mechanisms were studied; and the mitochondrial membrane potential (ΔΨm) was measured. Furthermore, in an EMs mouse model, the differentiation of macrophages in response to treatment with TC-conditioned medium (TCM) in vivo was studied. The results showed that upon in vitro co-culture with TCM, RAW264.7 cells differentiated more toward the M1 phenotype with enhancement of phagocytosis, increase in energy metabolism and proliferation owing to reduced the loss of ΔΨm, and suppression of dexamethasone-induced apoptosis. Further, along with the activation of NF-κB, Bcl-2 and Bcl-xl, the expression of Bax, cleaved-caspase9, and cleaved-caspase3 reduced in RAW264.7 cells. In addition, the M1 subtype was found to be the dominant phenotype among tissue and peritoneal macrophages in the EMs model subjected to in vivo TCM treatment. In conclusion, TCs enhanced M1 differentiation and phagocytosis while inhibiting apoptosis via the activation of NF-κB in macrophages, which potentially inhibited the onset of EMs. Our findings provide a potential research target and the scope for developing a promising therapeutic strategy for EMs.